The Important Role Of Fiqh Education In Elementary Schools - Nasiri (STID Raudlatul Iman Sumenep, 2025)
Education can be considered a crucial aspect of a nation's development process. Islamic religious education plays a crucial role in shaping students' character. Religious education is expected to facilitate students, starting from elementary school, in exploring and developing their faith potential from an early age. This will enable them not only to understand and apply their religious knowledge and faith, but also to live side by side with followers of other faiths. This will ultimately lead to Islam becoming not only the most populous religion in the world, but also a religion of mercy for the universe. Keywords: Islamic Religious Education, Elementary School